2018
DOI: 10.1017/s0022149x18000251
|View full text |Cite
|
Sign up to set email alerts
|

A new heligmonellid (Nematoda) species of the genus Stilestrongylus in Euryoryzomys russatus (Rodentia: Sigmodontinae) in the Atlantic Forest, southern Brazil

Abstract: A new species of Nippostrongylinae (Nematoda: Heligmonellidae), Stilestrongylus rolandoi n. sp., is described from specimens collected from the small intestine of the rodent Euryoryzomys russatus in the Atlantic Forest (Santo Amaro da Imperatriz, Santa Catarina state, southern Brazil). The genus Stilestrongylus includes 23 species, which parasitize rodents occurring in the Neotropical region. Stilestrongylus aureus (Durette-Desset & Sutton, 1985) from Argentina, S. azarai (Durette-Desset & Sutton, 1985) from A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Simões et al (2011) and Cardoso et al (2018) reported high prevalence values (> 40 %) of S. lanfrediae in this rodent in preserved and fragmented areas. The genus Stilestrongylus usually presents high prevalence, abundance and dominance in helminth communities of rodents (Simões et al 2011, Boullosa et al 2019, as observed in the present study. Simões et al (2011) described the first records of S. lanfrediae in the rodents A. montensis and A. cursor in the state of Rio de Janeiro.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Simões et al (2011) and Cardoso et al (2018) reported high prevalence values (> 40 %) of S. lanfrediae in this rodent in preserved and fragmented areas. The genus Stilestrongylus usually presents high prevalence, abundance and dominance in helminth communities of rodents (Simões et al 2011, Boullosa et al 2019, as observed in the present study. Simões et al (2011) described the first records of S. lanfrediae in the rodents A. montensis and A. cursor in the state of Rio de Janeiro.…”
Section: Discussionsupporting
confidence: 85%
“…The helminth species found in this study had previously been reported in sigmodontine rodents by Gomes et al (2003), Simões et al (2011), Kuhnen et al (2012), Panisse et al (2017) and Cardoso et al (2018), except for S. rolandoi. This species, found in the rodent E. russatus, was previously described in Boullosa et al (2019). Helminth species richness and species composition differed among the three rodents collected in the study area.…”
Section: Discussionmentioning
confidence: 50%
“…Considering the occurrence of the genus Stilestrongylus in E. russatus , four species of this genus were reported for this host, S. rolandoi, S. lanfrediae, S. kaaguyporai and S. evaginata ( Boullosa et al, 2019 ; Panisse and Digiani, 2018 ). The genus Syphacia was observed for this host by Kuhnen et al (2012) .…”
Section: Discussionmentioning
confidence: 99%
“…The genus Stilestrongylus is a common parasite group of sigmodontine rodents and has a strong coevolutionary history with these hosts (Simões et al ., 2011 ). Sigmodontine rodents infected by Stilestrongylus have been widely reported by several studies in different environments (Simões et al ., 2011 ; Panisse et al ., 2017 ; Boullosa et al ., 2019 ).…”
Section: Discussionmentioning
confidence: 99%